Comparative diffusion assay to assess efficacy of topical antimicrobial agents against Pseudomonas aeruginosa in burns care - Godreuil Sylvain; Bricard Françoise; Brabet Monique; Marchandin Hélène; Delage Milena; Romano Sara; Lebreton Françoise; Aujoulat Fabien; Parer Sylvie; Jumas-Bilak Estelle (BMC, 2011)
Abstract Background Severely burned patients may develop life-threatening nosocomial infections due to Pseudomonas aeruginosa, which can exhibit a high-level of resistance to antimicrobial drugs and has a propensity to cause nosocomial outbreaks. Antiseptic and topical antimicrobial compounds constitute major resources for burns care but in vitro testing of their activity is not performed in practice. Results In our burn unit, a P. aeruginosa clone multiresistant to antibiotics colonized or infected 26 patients over a 2-year period. This resident clone was characterized by PCR based on ERIC sequences. We investigated the susceptibility of the resident clone to silver sulphadiazine and to the main topical antimicrobial agents currently used in the burn unit. We proposed an optimized diffusion assay used for comparative analysis of P. aeruginosa strains. The resident clone displayed lower susceptibility to silver sulphadiazine and cerium silver sulphadiazine than strains unrelated to the resident clone in the unit or unrelated to the burn unit. Conclusions The diffusion assay developed herein detects differences in behaviour against antimicrobials between tested strains and a reference population. The method could be proposed for use in semi-routine practice of medical microbiology.